LIQUIDITY RATIO ANALYSIS AS AN ASSESSMENT TO MEASURE FINANCIAL PERFORMANCE AT PT GARUDA FOOD PUTRA PUTRI JAYA TBK - Fitrianingsih Fitrianingsih; Nurul Huda (Universitas Putera Batam, 2021)
A company's success can be measured based on the company's financial performance. The good and poor financial performance of the company can be assessed through the company's financial statements presented regularly. One way of assessing the financial performance of the most used companies is the financial ratio. Liquidity ratio is a ratio used to measure the company's ability to meet short-term liabilities (debt). This study aims to find out and analyze how well the current ratio (X1) to assess financial performance at PT. Garudafood Putra Putri Jaya, how good quick ratio (X2) to assess financial performance at PT. Garudafood Putra Putri Jaya, and how good the cash ratio (X3) to assess financial performance at PT. Garudafood Putra Putri Jaya. The type of research used is descriptive research with quantitative methods, Population in this study is financial report data for 5 years (2015-2019), sample in this study is 5 years, sampling technique is saturated sampling. The research instrument used is financial statements in the form of balance sheet reports accessed through the www.idx.co.id website. Data collection techniques are documentation and library studies. Based on the results of the research and hypothesis testing outlined earlier, the researchers drew the following conclusions: 1) The financial performance of PT Garudafood Putra Putri Jaya Tbk based on liquidity ratio is reviewed from the average current ratio of the company's condition is less than the expected criteria. 2) The financial performance of PT Garudafood Putra Putri Jaya Tbk based on liquidity ratio is reviewed from the average quick ratio of the company's condition is less than the expected criteria. 3) The financial performance of PT Garudafood Putra Putri Jaya Tbk based on liquidity ratio is reviewed from the average cash ratio of the company's condition is less than the expected criteria.